2008
DOI: 10.3998/ark.5550190.0009.d26
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneglycol an efficient solvent for stereoselective synthesis of β-amino ketones via direct Mannich reaction

Abstract: Polyethyleneglycol-2,4,6-Trichloro-1,3,5-Triazine (PEG 400-TCT) promotes a series of three component one-pot reactions of cyclohexanones with aromatic aldehydes and aniline. β-amino ketones are afforded in high yields and high stereoselectivity, in favor of the anti-isomer. Four new compounds are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…280 Mannich-type three-component one-pot reactions of cyclohexanones, aromatic aldehydes and aniline could be performed in PEG-400 in conjunction with 2,4,6-trichloro-1,3,5triazine as catalyst. 281 Lei and Hu 282 observed that a Biginellilike three-component condensation reaction of aromatic aldehyde, β-dicarbonyl compound and 2-aminobenzimidazole could be performed in water by using thiamine hydrochloride (VB 1 ), which is a nonflammable, inexpensive, and non-toxic reagent, as catalyst (Scheme 77). This method offers a straightforward and eco-friendly method for synthesizing benzo [4,5]imidazo[1,2-a]pyrimidine derivatives 134.…”
Section: Mcrs In Pegsmentioning
confidence: 99%
“…280 Mannich-type three-component one-pot reactions of cyclohexanones, aromatic aldehydes and aniline could be performed in PEG-400 in conjunction with 2,4,6-trichloro-1,3,5triazine as catalyst. 281 Lei and Hu 282 observed that a Biginellilike three-component condensation reaction of aromatic aldehyde, β-dicarbonyl compound and 2-aminobenzimidazole could be performed in water by using thiamine hydrochloride (VB 1 ), which is a nonflammable, inexpensive, and non-toxic reagent, as catalyst (Scheme 77). This method offers a straightforward and eco-friendly method for synthesizing benzo [4,5]imidazo[1,2-a]pyrimidine derivatives 134.…”
Section: Mcrs In Pegsmentioning
confidence: 99%
“…Thus, one-pot three-component reactions of aryl or cycloalkyl ketones with aryl aldehydes and aryl amines in ethanol at room temperature under catalytic conditions yielded the respective β-aminoketones 14a–q (Scheme 7). 85–92 The sequence of these reactions is related to Mannich-type reactions in a green protocol. The nanocatalyst activated the aldehyde ketone to nucleophilic attack by the amine group, and consequently enabled the enolization of the aryl or cycloalkyl ketones in the condensation.…”
Section: Synthetic Approachesmentioning
confidence: 99%